Produksi Dalam Ekonomi Islam - Nanik Nur Azizah (Journal of Islamic Banking, 2020)
In the economy, production activities are one of the activities that affect public consumption. Production is also an activity carried out to add value to an item or create new, useful goods. Producing an item is generally based on human needs. Production activities are carried out to meet consumer needs and to produce a maslahah for producers. Producers try to maximize production at a certain cost in order to obtain maximum profit. Likewise, consumers who meet their needs in an efficient manner, producers also want to meet their needs by producing goods at the cheapest cost. Apart from being profit-oriented, there are some of the producers who carry out their production in order to achieve mutual benefit in society. In this research, the author described the production from Islamic economics point of view. Keywords: Production, Producers, Islamic economics